IMPLEMENTASI METODE RAD PADA PERANCANGAN SISTEM MASJID PINTAR: STUDI KASUS MASJID AL-BUSTAMI - Yevi Grata Putra; Angga Madona; Tata Sutabri (ADISAM PUBLISHER, 2024)
The AL Bustami Mosque in Bukit Baru Village, Palembang City, faces various challenges in conventional management which have an impact on operational efficiency and effectiveness. These challenges include managing prayer schedules, assigning officers, managing donations, congregation data, and managing energy which is still done manually. To overcome this problem, a technology-based smart system was introduced, aimed at automating and integrating various aspects of mosque management. This research uses the Rapid Application Development (RAD) method to design and implement a smart system involving Internet of Things (IoT) technology, cloud computing, and big data analytics. The research results show that this smart system has succeeded in increasing the regularity of prayer schedules, management efficiency of the Mosque Prosperity Council (DKM), transparency in donation management, and more efficient energy management. The system implementation also received positive feedback from end users, namely mosque administrators and congregants. Overall, the